2013
DOI: 10.1007/s00345-013-1202-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective clamping under the usage of near-infrared fluorescence imaging with indocyanine green in robot-assisted partial nephrectomy: a single-surgeon matched-pair study

Abstract: Robot-assisted partial nephrectomy with selective clamping of the tumor feeding vascular branches is a promising technique for reduced ischemic renal trauma. This may lead to improved kidney function preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 23 publications
2
48
1
Order By: Relevance
“…Nohara et al [20] reported their results as mean change from baseline creatinine (mg/dl): global ischemia 0.15 versus regional ischemia 0.01, p = 0.012. Harke et al [17] reported their results as mean estimated glomerular filtration rate change from baseline (ml/min): global ischemia 16.1 versus regional ischemia 5.1, p = 0.045. Borofsky et al [18] also reported their results as mean estimated glomerular filtration rate change from baseline (%): global ischemia 14.9 versus regional ischemia 1.8, p = 0.03.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nohara et al [20] reported their results as mean change from baseline creatinine (mg/dl): global ischemia 0.15 versus regional ischemia 0.01, p = 0.012. Harke et al [17] reported their results as mean estimated glomerular filtration rate change from baseline (ml/min): global ischemia 16.1 versus regional ischemia 5.1, p = 0.045. Borofsky et al [18] also reported their results as mean estimated glomerular filtration rate change from baseline (%): global ischemia 14.9 versus regional ischemia 1.8, p = 0.03.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [8,17,18,19,20,21] reported margin status and one case [21] in global ischemia had a positive margin, while no cases in regional ischemia showed a positive margin (1 of 201 global ischemia cases vs. 0 of 162 regional ischemia cases).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations